Neuropharmacological Activities of Ceiba aesculifolia (Kunth) Britten & Baker f (Malvaceae) - Chrystyan Iván Bustos-Gómez; Deisy Gasca-Martínez; Eunice Yáñez-Barrientos; Sergio Hidalgo-Figueroa; Maria L. Gonzalez-Rivera; Juan Carlos Barragan-Galvez; Juan Ramón Zapata-Morales; Mario Isiordia-Espinoza; Alma Rosa Corrales-Escobosa; Angel Josabad Alonso-Castro (MDPI AG, 2022)
Ceiba aesculifolia (Kunth) Britten & Baker f (Malvaceae) is used for the folk treatment of mood disorders. C. aesculifolia bark was extracted in ethanol, and the extract (CAE) was chemically standardized using gas chromatography-mass spectrometry (GC-MS). This study evaluated the effects of CAE (10-100 mg/kg p.o.) on anxiolytic-like activity, sedation, locomotor activity, depression-like activity, and spatial working memory using in vivo rodent models. A possible mechanism for the anxiolytic-like and antidepressant-like actions induced by CAE was assessed using neurotransmission pathway inhibitors. Myristic acid was one of the compounds found in CAE using GC-MS. This study also evaluated the anxiolytic-like activity and the sedative actions of myristic acid and assessed a possible mechanism of action using neurotransmission pathway inhibitors and an in silico analysis. CAE elicited anxiolytic-like activity and antidepressant-like effects (ED50 = 57 mg/kg). CAE (10-100 mg/kg) did not affect locomotor coordination or induce sedation. The anxiolytic-like and antidepressant-like actions of CAE were reverted by prazosin, suggesting a possible participation of the noradrenergic system. The anxiolytic-like activity of myristic acid was reverted by the co-administration of prazosin and partially reverted by ketanserin. The docking study revealed that myristic acid can form favorable interactions within 5-HT2A and α1A-adrenoreceptor binding pockets.